Factors related with Hb 0 Vaccine Administration to Infant Age 0-7 days at The Sukawening Public Health Centre - Sukmawati S; Lilis Mamuroh; Furkon Nurhakim (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Background: Hepatitis is a public health problem in the world including Indonesia. Hepatitis B virus infected 2 billion people in the world, about 240 million of them become chronic hepatitis B sufferer, as many as 1,5 million world’s population died every year because of hepatitis. In 2013, immunization in Garut District accomplish (97,2%) HB 0 immunization, (106,7%) BCG, (97,8%) DPT/HB (3), (104,8%) Polio 4 and (102,9%) Measles. Although it exceeded above the determined target, HB 0 immunization still ranked the lowest compared to other immunization.Methods: This research aimed to analyzed factors related to HB 0 immunization including family income, attitudes, education level and knowledge on HB 0 immunization administration for infants aged 0-7 days at working area of Sukawening public health center. Number of sample in this research is 218 people. Data was obtained by interview using questionnaire, analyzed by multiple regression at α = 0,05.Result shows that there is a significant relationship between the mother's behavior of HB 0 immunization with family income variable (p-value 0,0320) attitude variable, education level and knowledge on HB 0 immunization has p-value < 0,000 for each at working area of Sukawening public health center. Variable that has the least influence is family income variable.Conclusion: Those factors influence mothers’ behavior on HB 0 immunization to their babies. Keywords: HB 0, Immunization, Infant